2004
DOI: 10.1111/j.1460-9568.2004.03527.x
|View full text |Cite
|
Sign up to set email alerts
|

Flies lacking all synapsins are unexpectedly healthy but are impaired in complex behaviour

Abstract: Vertebrate synapsins are abundant synaptic vesicle phosphoproteins that have been proposed to fine-regulate neurotransmitter release by phosphorylation-dependent control of synaptic vesicle motility. However, the consequences of a total lack of all synapsin isoforms due to a knock-out of all three mouse synapsin genes have not yet been investigated. In Drosophila a single synapsin gene encodes several isoforms and is expressed in most synaptic terminals. Thus the targeted deletion of the synapsin gene of Droso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
160
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 146 publications
(177 citation statements)
references
References 74 publications
15
160
0
1
Order By: Relevance
“…During periods of nerve activity, synapsin becomes phosphorylated, which reduces its affinity for vesicles (Huttner et al, 1983;TorriTarelli et al, 1992) and results in synapsin dispersion (Chi et al, 2001). Studies on terminals from animals lacking all synapsin genes [Drosophila larval muscle (Godenschwege et al, 2004); cultures of mouse CNS neurons (Gitler et al, 2004b)] found reduced synaptic vesicle numbers and reduced release during intense stimulation [especially in inhibitory synapses (Gitler et al, 2004b)] and support a model in which synapsin is particularly involved in anchoring vesicles belonging to the reserve pool (Hilfiker et al, 1999). None of these studies, however, addressed directly the core tenet of the synapsin hypothesis, namely that synapsin is the glue that regulates synaptic vesicle mobility.…”
Section: Introductionmentioning
confidence: 99%
“…During periods of nerve activity, synapsin becomes phosphorylated, which reduces its affinity for vesicles (Huttner et al, 1983;TorriTarelli et al, 1992) and results in synapsin dispersion (Chi et al, 2001). Studies on terminals from animals lacking all synapsin genes [Drosophila larval muscle (Godenschwege et al, 2004); cultures of mouse CNS neurons (Gitler et al, 2004b)] found reduced synaptic vesicle numbers and reduced release during intense stimulation [especially in inhibitory synapses (Gitler et al, 2004b)] and support a model in which synapsin is particularly involved in anchoring vesicles belonging to the reserve pool (Hilfiker et al, 1999). None of these studies, however, addressed directly the core tenet of the synapsin hypothesis, namely that synapsin is the glue that regulates synaptic vesicle mobility.…”
Section: Introductionmentioning
confidence: 99%
“…The syn 97 mutant strain carries the reported 1.4 kb deletion in the synapsin gene, removing part of the promote region, exon 1, and a small part of the first intron; consequentially, it lacks all Synapsin protein (Godenschwege et al 2004;Michels et al 2005). In the wild-type (WT) strain, we confirm expected Synapsin protein isoforms between 70 and 80 kDa and a weaker and variable band at 143 kDa (Klagges et al 1996).…”
Section: Genetic and Molecular Statusmentioning
confidence: 99%
“…In Drosophila, Synapsin is encoded by only one gene and is expressed in most if not all neurons of both the larval and adult nervous system (coding gene: syn, CG 3985: Klagges et al 1996;Michels et al 2005). Both adult and larval Drosophila lacking Synapsin show associative memory scores that are reduced by about half as compared with wild-type animals, as do animals upon an RNAi-mediated knockdown of Synapsin (adult odor-punishment memory: Godenschwege et al 2004;Knapek et al 2010;Niewalda et al 2015;Walkinshaw et al 2015; larval odor-reward memory: Michels et al 2005Michels et al , 2011. Corresponding phenotypes in learning and memory tasks have been reported throughout the animal kingdom, including man (Silva et al 1996;Garcia et al 2004;Südhof, 2004;Gitler et al 2008;Greco et al 2013).…”
mentioning
confidence: 99%
See 2 more Smart Citations